C-FPA: A Cloud-Based FPA Novel Approach to Defend Hotspot Issues and Attacks in WSN (Journal of Information Technology and Digital World, 2022)
Wireless Sensor Network (WSN) is a distributed network formed by sensor nodes that perform a specific sensing task like temperature, humidity, fire attacks, and so on. Used in all sorts of application like military, medical, industrial, scientific, and so on, WSN’s are well known for high performance operations. Till date, power conservation and sensor node lifetime remained as the major drawback in such networks where the development of optimization techniques and routing protocols were proposed to overcome them. Also, attacks like DoS (Denial Of Service), Sybil attack, wormhole attack, HELLO flood attack, and identity replication attack are mostly common in a WSN. At present, Hotspot-based issues and attacks is found as one of the major and performance-degrading factor in wireless sensor network. In this paper, we propose a novel cloud-based FPA scheme or approach to defend and withstand such hotspot-related issues and attacks in WSN. Developed with the principle of Cloud, the simulation results prove that the proposed scheme offer high privacy, and routing stability.
Keywords: Wireless sensor network; hotspot-locating attack; cloud; privacy; fake traffic; routing stability